Tratados bilaterales de inversión, privatizaciones y régimen de convertibilidad en la Argentina. Las semillas de las demandas ante el CIADI - VERBANAZ, Samuel (Papeles de Europa, 2011)
The Republic of Argentina has become the country with the highest number of claims made against it under the ICSID. This article attempts to analyze Argentina’s recent economic history which has resulted in unprecedented levels of claims made against it since 2002. This analysis draws upon three key elements which are considered not only relevant for their specific characteristics, as well as in the way they relate to each other: the intense privatization initiated in the 90s, the Bilateral Investment Treaties signed with major investor countries and the currency board.